2019
DOI: 10.1111/ina.12612
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the administered dose of particles on the facial mucosa of a realistic human model

Abstract: Exposure to particulate contaminants can cause serious adverse health effects. Deposition on the facial mucosa is an important path of exposure, but it is difficult to conduct direct dose measurement on real human subjects. In this study, we propose an in vitro method to assess the administered doses of micron‐sized particles on the eyes and lips in which computed tomographic scanning and three‐dimensional printing were used to create a model that includes a face, oropharynx, trachea, the first five generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
(95 reference statements)
0
15
0
Order By: Relevance
“…We developed a 3D-printed human replica ( Figure 1 ) based on computed tomography (CT) scans of the small airways of a healthy 34-year-old male, who is a non-smoker with no airway disease, to quantify the administered PM 2.5 dose [ 26 ]. The model includes the face, nasopharynx, trachea, G1–G5 bronchi and lung cavities.…”
Section: Methodsmentioning
confidence: 99%
“…We developed a 3D-printed human replica ( Figure 1 ) based on computed tomography (CT) scans of the small airways of a healthy 34-year-old male, who is a non-smoker with no airway disease, to quantify the administered PM 2.5 dose [ 26 ]. The model includes the face, nasopharynx, trachea, G1–G5 bronchi and lung cavities.…”
Section: Methodsmentioning
confidence: 99%
“…the model at a distance of 20 cm, found that more 80% of the generated aerosol particles with an initial velocity of 0.94 m/s was deposited on the lips rather than on the eyes [75].…”
Section: Gravitational Forcementioning
confidence: 96%
“…After entering into the respiratory system, large particles with large inertia may be trapped in the upper airways, while smaller particles with small inertia move along with the air and enter the lower airways [1,43,51,55,69,70]. The inhaled particles that fail to deposit in the respiratory system will be exhaled [42,44,48,[58][59][60][61][62][63][64][65][66]70]. RCMD particles may include a considerable amount of fine or ultrafine particles from which the most damaging particles are probably those that are small enough to penetrate deep into the lungs.…”
Section: Figurementioning
confidence: 99%